HUBUNGAN PENGGUNAAN EMOTICON PADA BLACKBERRY MESSENGER DENGAN EFEKTIFITAS KOMUNIKASI ANTAR PRIBADI (Studi Pada Remaja Usia Menengah Kelurahan Tanah Baru Bogor) - Risma Kartika; Nety Irianni (Jurnal Ilmu dan Budaya, 2018)
Development of information and communication technology very rapidly at this time to make, the more easy to communicate. Both orally and in writing, in oral communication one can determine the expression of the other person directly. Whereas in textual communications tend to be rigid, because it is not visible facial expressions that represent a person’a emotionc whilecommunicating. There are ways to reduce the stiffness in communication via text by using emoticons to facilitate users in effectiveness (improving quality) interpersonal communication using blackberry messenger emoticons through a more diverse to be able express my self, give and get the true meaning without having to meet. This study uses a positivist paradigm. This study uses a quantitative approach. Kind of research is explanative. The number of respondents in this study were 301 respondents based on those calculations slovin. Using a stratified sampling technique of middle age population as a teenager in 1205. Based kuisioner disseminated, the data can be found in the relationship (sig 0,011) between the level of effectiveness of the use of emoticons in interpersonal communications. Great relationship is 0,146. Thus it can be said that the use of emoticons to rate the effectiveness of interpersonal communication has a significant relationship and the direction of the positive.